2021
DOI: 10.1002/cti2.1273
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular macrophages create an intravascular niche for CD8+ T cell localisation prior to the onset of fatal experimental cerebral malaria

Abstract: Objectives The immunologic events that build up to the fatal neurological stage of experimental cerebral malaria (ECM) are incompletely understood. Here, we dissect immune cell behaviour occurring in the central nervous system (CNS) when Plasmodium berghei ANKA (PbA)‐infected mice show only minor clinical signs. Methods A 2‐photon intravital microscopy (2P‐IVM) brain imaging model was used to study the spatiotemporal context of early immunolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 77 publications
(151 reference statements)
0
26
0
Order By: Relevance
“…Initial tissue entry may be random, with the niche being assembled de novo at sites where incoming effector T cells happen to encounter cognate APCs in the perivascular space. The spatial relationship between these initial activation hubs and the infection foci itself is also not known, but it is likely that the initial activation event upon entry into the tissue will necessitate a subsequent relocation of that expanded effector T cell pool to the infection site for pathogen clearance, as previously predicted 119,122 …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Initial tissue entry may be random, with the niche being assembled de novo at sites where incoming effector T cells happen to encounter cognate APCs in the perivascular space. The spatial relationship between these initial activation hubs and the infection foci itself is also not known, but it is likely that the initial activation event upon entry into the tissue will necessitate a subsequent relocation of that expanded effector T cell pool to the infection site for pathogen clearance, as previously predicted 119,122 …”
Section: Discussionmentioning
confidence: 96%
“…A growing body of evidence points to the de novo assembly of microanatomical activation hubs located perivascularly that are induced following immune challenge and that underpin T cell immunity within inflamed tissues. 4,5,7,8,86,[117][118][119]…”
Section: Induced Activation Nichesmentioning
confidence: 99%
See 2 more Smart Citations
“…In normal condition, they are necessary for the maintenance of BBB, but in the case of CNS injury and neuroinflammation, they seem to mediate the damage of BBB. Most recently, PVMs have been confirmed to participate in BBB disruption through the release of cytotoxic mediators under malaria 90 . What's more, another review analyzed literature from 2000 to 2021 and revealed that PVMs could cause BBB damage in Alzheimer's disease (AD) 91 …”
Section: Pvm the First Line “Firewall” Maintaining The Homeostasis Of...mentioning
confidence: 99%